IDENTITY FORMATION OF THE CHILD MIGRANT IN MICHAEL ONDAATJE’S AUTOBIOGRAPHICAL NOVEL “THE CAT’S TABLE” - Vasylyna I. Khoma (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The current article examines the process of identity formation in the autobiographical novel “The Cat’s Table” by Michael Ondaatje, a Sri Lankan-born Canadian writer. The novel focuses on the childhood and youth stages, which are critical periods for transitioning into adulthood. The research aims to reconstruct the artistic depiction of the migrant character’s identity as they travel from East to West, taking into account the influence of location, environment, external factors, the experience of emigration and survival on the way to the formation of one’s own self. Research methods are subordinate to the aim of the study and tasks. The study employs literary analysis techniques such as close-reading, biographical and autobiographical analysis, narratology, postcolonial criticism, and identity studies. The objectives of the research include analyzing the novel’s poetics, thematic complexity, and genre specificity, examining the synthesis of autobiographical elements and motifs from postcolonial travel literature in relation to modern conceptualizations of identity, and exploring the processual nature of the identity formation of the author-narrator-migrant and the literary character-teen-migrant who exists in the “Third Space” according to H. Bhabha. The emigration of a child is seen as “rites of passage” proposed by Van Gennep, shared by the characters who have undergone international mobility in their early years. The article focuses on the transitional stage of identity acquisition by a child migrant, emphasizing that the writer draws from his own childhood experiences and attempts to convey his teenage identity crisis. The central character of the novel, an eleven-year-old boy, occurs on board a ship that travels from Sri Lanka, a colonized country, to the United Kingdom of Great Britain and Northern Ireland, the largest colonial state in the world in the 20th century. The sea voyage and events on the Oronsay, the ocean liner depicted in the novel, are based on the author’s real memories and serve as a means to delve into the inner journey of the past and reconstruct childhood memories. The concept of “identity crisis”, as described by E. Erikson, is viewed not as a catastrophic event but as a pivotal moment of development that reflects the complexities of social identity and personal growth during the transitional age. The article concludes that the experience of migration during the formative years of personal identity, shared by the author and the characters, is crucial for the adaptation strategies of individuals undergoing resettlement and serves as a significant motif in postcolonial literature focused on the lives of migrants.